ANALISIS PENINGKATAN MUTU GURU SMP NEGERI SATU ATAP LANGKOMU KECAMATAN MAWASANGKA TENGAH KABUPATEN BUTON - Arsadi - (JI@P, 2015)
Arsadi, 2015. “Analysis on the quality improvement of the teachers of One-Stop State Junior High School (SMP Negeri Satu Atap) of Langkomu ofMawasangka Tengah Sub District of Buton Regency.Corresponding to the reality in One-Stop State Junior High School (SMPNegeri Satu Atap) Langkomu of Mawasangka Tengah Sub District of ButonRegency, the background of problem in this research is an inadequateempowerment of teacher competency, in which every teacher teaches morethan one subject, poor learning administration, poor knowledge andinfrastructure supporting learning in which the society culture builds onlearning concept at school. The objective of research was to find out the roleof headmaster in improving the teacher quality in SMP Negeri Satu AtapLangkomu of Mawasangka Tengah Sub District of Buton Regency. Theresearch method employed in this study was qualitative researh. The researchwas taken place in SMP Negeri Satu Atap Langkomu of Mawasangka TengahSub District of Buton Regency. The research was conducted within threemonths, from April to June, 2014. The research procedure started fromresearch preparation, proposal seminar, instrument development, instrumenttrial, data collection of the quality improvement and of the teacher attitudetoward their own works and upon their professional competency, dataanalysis, and ended with research instrument development. The datacollection was conducted using observation, documentation and interviewmethods. Then, the technique of analyzing data used included ordering thedata, organizing them into some pattern, category, and basic elaboration unit.Thus the interpretation could be made, giving significant meaning to analysis,explaining the elaboration pattern, and looking for the relationship betweenelaboration dimensions.Keywords: Role of headmaster, teacher quality Improvement, proffessionalcompetency.